Sonographic assessment of kidneys and associated abdominal findings in patients with renal parenchymal diseases - Gareeballah, Awadia; Gameraddin, Moawia Bushra; Salih, Suliman; Tamboul, Jumaa (International Journal of Research in Medical Sciences, 2017)
Background: The renal parenchymal diseases were common pathological conditions that involved the renal parenchyma. They cause damage to interstitia and glomerula and result in renal failure if left undiagnosed and untreated. The objective of the study was to assess the kidneys in renal parenchymal diseases in Sudanese patients. Methods: This cross-sectional study involved two hundred and six patients confirmed with renal parenchymal diseases. All the patients were scanned using ultrasonography. The echogenicity, kidney size, surface and thickness of renal cortex were assessed and the related abdominal findings. Results: A total of 206 patients diagnosed and confirmed renal parenchymal diseases had been selected for the study. The kidneys were normal in size in 47.10% the cases, 30.58% were small and 19.42% were large. The echogenicity of the kidneys was increased in 93.69% and normal echogenicity observed in 5.34% of the cases. The renal cortical thickness was normal in 65.05% and thin in 33.50% of the cases. There were no obstructive changes in the renal pelvicalyceal system in 86.41%, while dilatation observed only in 7.28% of the cases. Abdominal findings were observed in 65.05% of the cases. The most common abdominal findings were 26 cases of ascites, 10 with pleural effusion, 6 with benign prostatic hypertrophy and 4 with liver cirrhosis. Conclusions: Sonographic evaluation of kidneys in renal parenchymal diseases is very important in diagnosis and management. Pleural effusion, ascites and liver cirrhosis were the most common systematic findings accompanied with renal parenchymal diseases.